Company Value - Analysis from the LQ45 Company Financial Perspective for 2020-2023 - Farid Muhammad Rofifudin; Ayu Setiyawan; Nurul Aisah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – This analysis will cover various industrial sectors to obtain a comprehensive picture of how companies in Indonesia responded to the challenges and opportunities that emerged during this period. Research data is secondary data from the financial report of the company in Indonesia. Aim – The aim of this research is to analyse the development of the company value in Indonesia during the 2020-2023 period. Design / Methodology / Approach – This research uses secondary data from the financial report of the company in Indonesia. The population used uses purposive sampling and time series methods. Findings – The results of this research state that capital structure and profitability have a significant influence on company value, with a fairly strong negative impact. Investment decisions and dividend policy do not show a significant influence in the context of LQ45 companies. Conclusion - To increase firm value, focusing on effective management of profitability and capital structure may be more strategic Research implication – This research will also explore the factors that contribute to changes in company value to help investors make smarter investment decisions. Limitations – The limitations of this research are (a) The sample includes companies that are on the LQ45 BEI index for 2020-2023, (b) The sample publishes audited annual financial reports in 2020-2023, (c) The sample is a company that generates positive profits and distributes dividends.